2020
DOI: 10.3389/fchem.2020.581198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UV/H2O2, UV/PMS, and UV/PDS in Destruction of Different Reactivity Compounds and Formation of Bromate and Chlorate

Abstract: In this study, we compared the decontamination kinetics of various target compounds and the oxidation by-products (bromate and chlorate) of PMS, PDS, and H 2 O 2 under UV irradiation (UV/PMS, UV/PDS, UV/H 2 O 2). Probes of different reactivity with hydroxyl and sulfate radicals, such as benzoic acid (BA), nitrobenzene (NB), and trichloromethane (TCM), were selected to compare the decontamination efficiency of the three oxidation systems. Experiments were performed under acidic, neutral, and alkaline pH conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…Despite the lower BrO 3 – formation yields observed with heat/PMS-Cl – , the BrO 3 – levels detected under varying R Cl/Br conditions (Figure S16) substantially exceeded the maximum contaminant level for BrO 3 – in drinking water (10 μg/L) in most cases. This appears to be linked with the earlier findings that the use of persulfate instead of H 2 O 2 in photoinduced activation facilitated the occurrence of oxyhalides such as ClO 3 – and BrO 3 – . , BrO 3 – more effectively formed during persulfate activation due to (i) the preferred one-electron oxidation of Br – by SO 4 •– and (ii) direct oxidation of Br – to HOBr by PMS . As a countermeasure to mitigate BrO 3 – formation, the potentials roles of PMS and SO 5 •– /S 2 O 8 •– in scavenging X • /X 2 •– and reducing HOBr, respectively, could be explored.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Despite the lower BrO 3 – formation yields observed with heat/PMS-Cl – , the BrO 3 – levels detected under varying R Cl/Br conditions (Figure S16) substantially exceeded the maximum contaminant level for BrO 3 – in drinking water (10 μg/L) in most cases. This appears to be linked with the earlier findings that the use of persulfate instead of H 2 O 2 in photoinduced activation facilitated the occurrence of oxyhalides such as ClO 3 – and BrO 3 – . , BrO 3 – more effectively formed during persulfate activation due to (i) the preferred one-electron oxidation of Br – by SO 4 •– and (ii) direct oxidation of Br – to HOBr by PMS . As a countermeasure to mitigate BrO 3 – formation, the potentials roles of PMS and SO 5 •– /S 2 O 8 •– in scavenging X • /X 2 •– and reducing HOBr, respectively, could be explored.…”
Section: Resultsmentioning
confidence: 54%
“…− and BrO 3 − . 57,58 BrO 3 − more effectively formed during persulfate activation due to (i) the preferred one-electron oxidation of Br − by SO 4…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, NOM also could scavenge SO 4 •- under UV/PDS [12] . Meanwhile, the scavenging effect of NOM on SO 4 •- was also significant [15] , [16] . But based on our calculations, we found the contribution of sulfate radicals to the degradation of ribavirin is slightly increased from 0.03 to 0.06%.…”
Section: Resultsmentioning
confidence: 94%
“…The data revealed that the ε values for H2O2 and its dissociated form HO2 − were 19.6 and 229 M −1 cm −1 were higher than those for HSO5 − (the monovalent form of PMS) and SO5 2− , the divalent form of PMS (13.8 and 149.5 M −1 cm −1 , respectively). Furthermore, the quantum yield of H2O2 photolysis at 254 nm was determined to be Φ = 0.5, whereas the quantum yield of PMS photolysis at the same wavelength was measured as Φ = 0.52 [58]. Consequently, the slightly better performance of the UV/PMS/H2O2 system can be attributed to the efficient absorption of UV light facilitating H2O2 and PMS photolysis, which leads to an increased amount of ROS.…”
Section: Degradation Of Sunscreen Agents In Ultrapure Water By Uv-dri...mentioning
confidence: 98%